Perbedaan Kecemasan Pasien Pre Regional Anestesi Sebelum dan Sesudah Pemberian Edukasi Video SAB - Ahmad Zainullah; Wijayanti Wijayanti; Sri Mintarsih; Nur Rofiq Al Ghiffari (An-Najat, 2024)
Background: Surgery is a medical procedure that uses invasive techniques by opening or displaying the body part to be treated through an incision that ends with closing and suturing the wound. That 90% of patients who will undergo surgery experience anxiety.) Health education about surgical preparation is needed to anticipate unwanted anxiety levels. If the patient's knowledge is good about surgical preparation, then the patient can improve their coping skills against anxiety. Audio-visual tools have very good sophistication because they can provide stimulation to sight and hearing in receiving information that can be seen and heard. Purpose: This study aims to determine the effect of providing SAB educational videos on anxiety in patients with regional anesthesia. Research Methods: This study is a pre-experiment with a one group pretest and post-test design. The sampling technique in this study was Purposive sampling, This study was conducted in April - May 2024. Results: Based on the Paired Test obtained sig (2-tailed) of 2.75x10-9 which means less than 0.05, it is concluded that the provision of SAB videos affects the level of patient anxiety when undergoing pre-regional anesthesia. Conclusion: There is a difference in anxiety in patients with Pre-Regional Anesthesia before and after the provision of SAB video education.